What is New in Pediatric Orthopaedic: Basic Science. Issue 2 (21st February 2023) - Lynch, Brian; Botros, Daniel; Halanski, Matthew; Barsi, James
Abstract : Background: An understanding of musculoskeletal basic science underpins most advancements in the field of orthopaedic surgery. Knowledge of biomechanics, genetics, and molecular pathways is integral to the understanding of the pathophysiology of disease and guides novel treatment options to improve patient outcomes. The purpose of this review is to provide a comprehensive and current overview of musculoskeletal basic science relevant to pediatric orthopaedic surgery. Methods: Comprehensive Pubmed database searches were performed for all English language articles published between January 2016 and November 2021 using the following search terms: basic science, pediatric orthopaedics, fracture, trauma, spine, scoliosis, DDH, hip dysplasia, Perthes, Legg-Calve-Perthes, clubfoot, and sports medicine. Inclusion criteria focused on basic science studies of pediatric orthopaedic conditions. Clinical studies or case reports were excluded. A total of 3855 articles were retrieved. After removing duplicates and those failing to meet our inclusion criteria, 49 articles were included in the final review. Results: A total of 49 papers were selected for review based on the date of publication and updated findings. Findings are discussed in the subheadings below. Articles were then sorted into the following sub-disciplines of pediatric orthopaedics: spine, trauma, sports medicine, hip, and foot. Conclusions: With this review, we have identified many exciting developments in pediatric orthopaedic trauma, spine, hip, foot, and sports medicine that could potentially lead to changes in disease management and how we think of these processes. Level of Evidence: Level V